Assessment of the HER2, PDL1 and oxidative stress levels at the menopausal status of newly diagnosed breast cancer patients - Mahmood, Baraa R.; Allwsh, Thikra A. (Journal of Contemporary Medical Sciences, 2022)
Objective: This study aimed to estimate the levels of HER2, PD-L1 and oxidative stress in newly diagnosed breast cancer patients. Also, to estimate the probability of using HER2 and PD-L1 as a predictive marker on the occurrence of breast cancer in addition to study the effect of menopausal status at the level of HER2, PD-L1, oxidative stress and breast cancer risk factor. Methods: This study included 125 newly diagnosed breast cancer patients (53 premenopausal and 72 postmenopausal) from Oncology and Nuclear Medicine Hospital in Mosul, Iraq, and 100 apparently healthy women as a control group (44 premenopausal and 56 postmenopausal), during the period from Jan. 2021 to Jun. 2021. The ages of patients and control are matched, and it is ranged from 30-60 years. In this study we estimate the level of Human Epidermal Growth Factor Receptor 2 (HER2), Programmed Death -Ligand 1(PD-L1), total antioxidant capacity (T-AOC), arylesterase activity, uric acid level, malondialdehyde (MDA) level, peroxidase activity, lactoperoxidase activity and iron level at breast cancer patients and control. Results: The results show that there is a significant elevation in the level of HER2, PD-L1, malondialdehyde, peroxidase, lactoperoxidase and iron, and a significant decrease in the level of T-AOC, arylesterase and uric acid in the serum of breast cancer patients (pre and postmenopausal) compared with the control group (pre and postmenopausal). Also, increase the level of HER2 and oxidative stress at postmenopausal status for the control and patient groups. while PD-L1 level does not affect by menopausal status for both control and patient groups. Conclusion: The level of HER2, PD-L1, and oxidative stress was significantly increased in newly diagnosed breast cancer patients compared with the control group at the same menopausal status. Increase breast cancer risk factor at the postmenopausal status.